CALCULATION TO DETERMINE INPUT-OUTPUT LINEARIZATION OF NONLINEAR SYSTEMS - DWIPANTOPO (NIM : 10109033); pembimbing : Dr. Janson Naiborhu, ODIT
A system, in particular nonlinear system, will have the possibility to unstable. One strategy to overcome this problem is by using input-output linearization, in other word is to find a linear relation between input and output. The nonlinear system will be transformed into Byrness-Isidori Normal Form. The system must be transformed first, after that the system will be separated into stable and antistable part. So we get Special Byrness-Isidori Normal Form. This thesis will be performed computation of the change of coordinates that directly transform nonlinear system to Special Byrness-Isidori Normal Form, so that the system directly separated into stable and antistable part.